Development of preimplantation genetic testing for monogenic reference materials using next-generation sequencing - Weihua Zhao; Yanyan Song; Chuanfeng Huang; Shan Xu; Qi Luo; Runsi Yao; Nan Sun; Bo Liang; Jia Fei; Fangfang Gao; Jie Huang; Shoufang Qu (BMC, 2024)
Abstract Objective Preimplantation genetic testing for monogenic disorders (PGT-M) has been used for over 20 years to detect many serious genetic conditions. However, there is still a lack of reference materials (RMs) to validate the test performance during the development and quality control of PGT-M. Method Sixteen thalassemia cell lines from four thalassemia families were selected to establish the RMs. Each family consisted of parents with heterozygous mutations for α- and/or β-thalassemia and two children, at least one of whom carried a homozygous thalassemia mutation (proband). The RM panel consisted of 12 DNA samples (parents and probands in 4 families) and 4 simulated embryos (cell lines constructed from blood samples from the four nonproband children). Four accredited genetics laboratories that offer verification of thalassemia samples were invited to evaluate the performance of the RM panel. Furthermore, the stability of the RMs was determined by testing after freeze‒thaw cycles and long-term storage. Results PGT-M reference materials containing 12 genome DNA (gDNA) reference materials and 4 simulated embryo reference materials for thalassemia testing were successfully established. Next-generation sequencing was performed on the samples. The genotypes and haplotypes of all 16 PGT-M reference materials were concordant across the four labs, which used various testing workflows. These well-characterized PGT-M reference materials retained their stability even after 3 years of storage. Conclusion The establishment of PGT-M reference materials for thalassemia will help with the standardization and accuracy of PGT-M in clinical use.